Análise do comportamento do Ibovespa e Ifix frente às oscilações de variáveis macroeconômicas - Rocha, Laura Antunes (Universidade Federal de São Carlos, 2023)
The aim of the present study is to understand how the Ibovespa and IFIX indices behave in response to movements in some of the key macroeconomic variables, namely the Selic interest rate, IPCA inflation rate, exchange rate, and a measure of economic output, in order to discern the degree of relationship between these variables. To accomplish this objective, a review of the existing literature was conducted, delving into the macroeconomic context. Furthermore, time series modeling techniques were employed to quantify the relationships among the variables under investigation. As the main outcome of this effort, it was identified that the Ibovespa and IFIX indices may be influenced, albeit not significantly, by changes in the assessed macroeconomic variables, with particular emphasis on the output gap and IPCA inflation rate, which emerged as the most relevant variables for the indices in question. Such findings contribute significantly to the understanding of the complex dynamics between financial indices and macroeconomic variables, carrying important implications for investors, decision-makers, and professionals in the economic field.
Analysis of the behavior of the Ibovespa and Ifix in response to macroeconomic variables fluctuations
Keywords: Mercados de Capitais; Variáveis Macroeconômicas; Ibovespa; IFIX; Capital Markets; Macroeconomic Variables; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::ECONOMIA MONETARIA E FISCAL::INSTITUICOES MONETARIAS E FINANCEIRAS DO BRASIL